Waspadai Bahaya Kriminalisasi pada Anak Usia Dini - Hafizah Tulaini (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Abstract, The criminalization of early childhood in the family environment has become a worrying issue in the modern era. This phenomenon occurs when young children experience negative treatment or stigma which can lead to labeling or exclusion in the home environment, whether consciously or not. Various actions that are considered